Assessing Cerebral Glucose Metabolism in Patients with Idiopathic Rapid Eye Movement Sleep Behavior Disorder. Issue 11 (November 2015) - Ge, Jingjie; Wu, Ping; Peng, Shichun; Yu, Huan; Zhang, Huiwei; Guan, Yihui; Eidelberg, David; Zuo, Chuantao; Ma, Yilong; Wang, Jian
Correction to : Journal of Cerebral Blood Flow and Metabolism advance online publication, 29 July 2015; doi:10.1038/jcbfm.2015.173. Following the online publication of this article, the authors noted that the order of the appearance of affiliations and the information of the correspondence were placed incorrectly. The affiliations of the authors and the order of the correspondence have been reordered as follows: Jingjie Ge 2, 4, Ping Wu 2, 4, Shichun Peng 3, Huan Yu 1, Huiwei Zhang 2, Yihui Guan 2, David Eidelberg 3, Chuantao Zuo 2, Yilong Ma 3, 5, Jian Wang 1, 5 1 Department of Neurology, Huashan Hospital, Fudan University, Shanghai, China; 2 PET Center, Huashan Hospital, Fudan University, Shanghai, China and 3 Center for Neurosciences, The Feinstein Institute for Medical Research, North Shore-Long Island Jewish Health System, Manhasset, New York, USA. Correspondence: Dr J Wang, Department of Neurology, Huashan Hospital, Fudan University, No. 12 Middle Wulumuqi Road, Jing'an District, Shanghai 200040, China or Dr Y Ma, Center for Neurosciences, The Feinstein Institute for Medical Research, 350 Community Drive, Manhasset, New York 11030, USA. 4 These authors contributed equally to this work. 5 These authors shared senior authorship. E-mail:wangjian336@hotmail.com oryma@nshs.edu